2016
DOI: 10.3390/w8070295
|View full text |Cite
|
Sign up to set email alerts
|

A Lymnaea stagnalis Embryo Test for Toxicity Bioindication of Acidification and Ammonia Pollution in Water

Abstract: Abstract:The paper presents a study leading to a new acute toxicity test on embryonic and juvenile organisms of the great pond snail (Lymnaea stagnalis Linnaeus). Sulfuric acid, nitric acid, and ammonium hydroxide were used as waterborne toxicants in laboratory experiments. The exposure time was 24 h. Tests were conducted in 5-10 replications for each toxicant. The toxicity of the substances was classified according to different scales and the test's sensitivity was compared to that of the commonly used bioind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
9
1
Order By: Relevance
“…Unfortunately, the morphological identi cation for Epheomeptera is highly challenging for many benthic macroinvertebrates. Also, several studies (Patrick 2015;Mazur et al 2016) reported that Lymnaeidae could tolerate water with low DO, the CCA result of this study was not able to validate it.…”
Section: Benthic Macroinvertebrates and Environmental Variablescontrasting
confidence: 80%
“…Unfortunately, the morphological identi cation for Epheomeptera is highly challenging for many benthic macroinvertebrates. Also, several studies (Patrick 2015;Mazur et al 2016) reported that Lymnaeidae could tolerate water with low DO, the CCA result of this study was not able to validate it.…”
Section: Benthic Macroinvertebrates and Environmental Variablescontrasting
confidence: 80%
“…Also, as a widely-distributed organism in freshwater ecosystems all over the world, L. stagnalis has recently been adopted as the model species of a new OECD test guideline [ 8 ]. It has been used as a biomonitor for the effects of a variety of water conditions and pollutants, including heavy metals [ 9 , 10 ], water acidification [ 11 ], and pesticide use [ 12 , 13 ]. Finally, L. stagnalis is relatively closely related to the land snail Biomphalaria glabrata , a vector for Schistosoma mansoni , the parasite that is the cause for schistosomiasis [ 14 ], a prominent public health burden in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Due to differing levels of non-coding RNA annotation for each species, we have focused our analyses on protein-coding transcripts. Annotation of the top 20 expressed transcripts in each of these ve species (Table S7- 11), in the same manner as done for L. stagnalis (Table 1), found a predominance of transcripts involved in energy production, protein synthesis, and signaling, in both vertebrate and invertebrate species. To gain a complementary perspective, we characterized the functional categorization of CNS protein-coding transcripts amongst L. stagnalis and these ve common model organisms ( Figure 3) using their KOG annotations.…”
Section: Comparisons Of Cns Transcriptomes Of Key Neuroscience Model mentioning
confidence: 94%
“…Also, as a widely-distributed organism in freshwater ecosystems all over the world, L. stagnalis has recently been adopted as the model species of a new OECD test guideline [8]. It has been used as a biomonitor for the effects of a variety of water conditions and pollutants, including heavy metals [9,10], water acidi cation [11], and pesticide use [12,13]. Finally, L. stagnalis is relatively closely related to the land snail Biomphalaria glabrata, a vector for Schistosoma mansoni, the parasite that is the cause for schistosomiasis [14], a prominent public health burden in developing countries.…”
Section: Introductionmentioning
confidence: 99%